Research hotspots and trends in visceral pain research: A global comprehensive bibliometric analysis - Guan, Le; Liu, Yang; Wu, Bin; Chen, Aiqin; Tao, Wucheng; Lin, Chun (Frontiers in Molecular Neuroscience, 2023)
Background Visceral pain is a complex and heterogeneous disorder that is considered more prominent compared to somatic pain, due to its multiple and complex causes and accompanying emotional and mood disorders. Research has become increasingly extensive over the years, but a bibliometric analysis of this field is lacking. The aim of this study was to analyze global research trends in visceral pain over the past 40 years through visual analysis. Methods We conducted a comprehensive search of the literature from January 1981 to December 2021 using the Web of Science core database. The medical subject term ‘visceral pain’ was searched. We used CiteSpace and VOSviewer for bibliometric analysis and network visualization, including top-ranked authors, keywords, research collaborations, and literature co-occurrence network analysis. Results A total of 5,047 articles were included in the analysis. The number of articles on visceral pain has continued to grow steadily over the past 40 years. The United States (1,716 articles), University of California (159 articles), and Neurogastroenterology and Motility (276 articles) were the country, institution, and journal with the most publications, respectively. Keyword analysis showed that inflammation, visceral hypersensitivity, inflammatory bowel disease (IBD), irritable bowel syndrome (IBS), anxiety, and quality of life were the research trends and priorities in this research field. Conclusion Visceral pain-related research has received increasing attention in recent decades. However, there are still many unresolved issues in the field of visceral pain, such as the specific molecular mechanisms and clinical treatments between visceral pain and inflammation, IBD, IBS, anxiety, and quality of life, which may require further exploration based on modern scientific and technological means and more basic research, especially for the therapeutic targets of visceral pain, which may become a hot spot for future research and provide guidance for the treatment of clinical diseases related to visceral pain.